The Effect of Specialized Transitional Speed on Developing some Offensive Variables for the Youth Football Pivot Player - Hasan, Ahmed Qays; Khan, Ahmed Abbas Ali (Pubmedia Jurnal Pendidikan Olahraga, 2025)
Every study endeavor is driven by a specific goal that researchers aim to achieve. The present study seeks to design specialized transitional speed exercises and subsequently examine their effectiveness in developing selected offensive variables for the youth football pivot player. Transitional speed is considered one of the most critical physical attributes that distinguish athletes across various sports disciplines. It is defined as the ability to move swiftly from one location to another, it also requires a combination of strength, speed, and endurance. In this context, the study explores the significance of transitional speed in different sports and how to develop and enhance it among athletes. The experimental method was employed using a one-group design with pre- and post-tests. The sample of the study consisted of pivot players from Al-Miqdadiya Football Club, with the experimental group comprising two pivot players from the club. Additionally, a pilot sample included one pivot player outside the main study sample. Following the administration of tests, implementation of the primary training experiment, and achievement of results and statically analyzing them, the researchers came up with the following key conclusions: transitional speed exercises proved effective in improving selected offensive variables for youth football pivot players. The researchers recommend palcing greater emphasis on the development of the pivot player, both defensively and offensively.